Registered Apprenticeship and Career Advancement for Low-Wage Service Workers. Issue 2 (May 2019) - Kuehn, Daniel
Registered apprenticeship is a time-tested approach to building technical skills through a combination of classroom and closely supervised on-the-job training. This study explores the growth of registered apprenticeship in service occupations over the past two decades and uses administrative data on registered apprentices to identify the factors associated with successful program completion and exit wage growth. Key program characteristics vary across different service occupations, but shorter apprenticeship programs operated by single employers working jointly with a union seem to be consistently associated with higher completion rates. Partnerships with community colleges fail to generate higher completion rates, although for many service occupations these partnerships are associated with higher exit wages.